ADHD and risk for subsequent adverse childhood experiences: understanding the cycle of adversity. (2nd December 2020) - Lugo‐Candelas, Claudia; Corbeil, Thomas; Wall, Melanie; Posner, Jonathan; Bird, Hector; Canino, Glorisa; Fisher, Prudence W.; Suglia, Shakira F.; Duarte, Cristiane S.
Abstract : Background: Children with adverse childhood experiences (ACEs) are more likely to develop Attention‐Deficit/Hyperactivity Disorder (ADHD). The reverse relationship – ADHD predicting subsequent ACEs – is vastly understudied, although it may be of great relevance to underserved populations highly exposed to ACEs. Methods: Participants were 5‐ to 15‐year‐olds (48% females) with (9.9%) and without ADHD (DSM‐IV criteria except age of onset) in a longitudinal population‐based study of Puerto Rican youth. In each wave (3 yearly assessments, W1‐3), ten ACEs (covering parental loss and maladjustment and child maltreatment) were examined, plus exposure to violence. Logistic regression models examined ADHD (including subtypes) and subsequent risk for ACEs. Also considered were interactions by age, sex, number of W1 ACEs, and recruitment site. Results: Children with W1 ADHD were more likely to experience subsequent adversity (OR: 1.63; 95% CI: 1.12–2.37) accounting for child age, sex, public assistance, maternal education, site, disruptive behavior disorders, and W1 ACEs. Inattentive (OR: 2.00; 95% CI: 1.09–3.66), but not hyperactive/impulsive or combined ADHD, predicted future ACEs. Conclusions: ADHD predicts subsequent risk for ACEs, and the inattentive presentation may confer the most risk. Inattentive presentations could pose a bigger risk given differences in symptom persistence, latency to access to treatment, and treatment duration. The present study suggests a pathway for the perpetuation of adversity, where bidirectional relationships between ADHD and ACEs may ensnare children in developmental pathways predictive of poor outcomes. Understanding the mechanism underlying this association can help the development of interventions that interrupt the cycle of adversity exposure and improve the lives of children with ADHD.